Autosomal-dominant adult neuronal ceroid lipofuscinosis caused by duplication in DNAJC5 initially missed by Sanger and whole-exome sequencing - Jedličková, Ivana; Cadieux-Dion, Maxime; Přistoupilová, Anna; Stránecký, Viktor; Hartmannová, Hana; Hodaňová, Kateřina; Barešová, Veronika; Hůlková, Helena; Sikora, Jakub; Nosková, Lenka; Mušálková, Dita; Vyleťal, Petr; et al. (European journal of human genetics, 2020)
Adult-onset neuronal ceroid lipofuscinoses (ANCL, Kufs disease) are rare hereditary neuropsychiatric disorders characterized by intralysosomal accumulation of ceroid in tissues. The ceroid accumulation primarily affects the brain, leading to neuronal loss and progressive neurodegeneration. Although several causative genes have been identified (DNAJC5, CLN6, CTSF, GRN, CLN1, CLN5, ATP13A2), the genetic underpinnings of ANCL in some families remain unknown. Here we report one family with autosomal dominant (AD) Kufs disease caused by a 30 bp in-frame duplication in DNAJC5, encoding the cysteine-string protein alpha (CSPα). This variant leads to a duplication of the central core motif of the cysteine-string domain of CSPα and affects palmitoylation-dependent CSPα sorting in cultured neuronal cells similarly to two previously described CSPα variants, p.(Leu115Arg) and p.(Leu116del). Interestingly, the duplication was not detected initially by standard Sanger sequencing due to a preferential PCR amplification of the shorter wild-type allele and allelic dropout of the mutated DNAJC5 allele. It was also missed by subsequent whole-exome sequencing (WES). Its identification was facilitated by reanalysis of original WES data and modification of the PCR and Sanger sequencing protocols. Independently occurring variants in the genomic sequence of DNAJC5 encoding the cysteine-string domain of CSPα suggest that this region may be more prone to DNA replication errors and that insertions or duplications within this domain should be considered in unsolved ANCL cases.
Keywords: duplikace genu; dospělí; Gene Duplication; Protein Transport; membránové proteiny; transport proteinů; buněčné linie; Genetic Testing; Humans; Membrane Proteins; lidé středního věku; Cell Line; Middle Aged; Mice; zvířata; Protein Processing, Post-Translational; neuronální ceroidlipofuscinózy; Whole Genome Sequencing; mužské pohlaví; HSP40 Heat-Shock Proteins; Neurons; Adult; posttranslační úpravy proteinů; Neuronal Ceroid-Lipofuscinoses; False Negative Reactions; sekvenování celého genomu; myši; ženské pohlaví; proteiny tepelného šoku HSP40; falešně negativní reakce; Animals; lidé; neurony; Male; genetické testování; Female